Prolonged esophageal foreign body: Management strategies in the setting of complicated tracheoesophageal fistula - Krista Kiyosaki; James Wall; Douglas R. Sidell (Elsevier, 2019)
Esophageal coins rarely migrate extraluminally or cause systemic illness and the development of tracheoesophageal fistulae (TEF) secondary to coin ingestion is rare. When they do occur, surgical repair may be complicated by a contaminated operative site and systemic instability. As a means to review treatment options in this setting, we present a rare case of a 16-year-old female with a history of longstanding esophageal foreign body complicated by a large tracheoesophageal fistula, mediastinitis, and sepsis. She was ultimately managed by means of endoscopic diversion and tracheal stenting to reduce wound contamination in preparation for definitive open repair. A comprehensive literature review is performed and our approach to this patient's management is discussed. In the setting of a mediastinal leak, infection and systemic instability, endoscopic techniques and novel clip applicators may be employed to control wound contamination prior to definitive repair. Keywords: Tracheoesophageal fistula, Esophageal foreign body, Endoscopy, Bronchoscopy, Esophagoscopy, Tracheal stent, Mediastinitis